Faktor – Faktor Yang Berhubungan Dengan Kepatuhan Perawat Dalam Melakukan Hand Hygiene Di Rumah Sakit Ummuhani Purbalingga - Ani Wahyuni; Etlidawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Hand hygiene is the most effective method for preventing healthcare-associated infections. However, its practice is still not optimally implemented in many healthcare facilities. Several factors may influence compliance levels, including age, gender, education, length of work experience, knowledge, attitude, and availability of supporting facilities. Objective: This study aimed to identify factors associated with nurses compliance in performing hand hygiene at RSIA (Obstetric and Pediatric Hospital) Ummuhani Purbalingga. This qualitative study employed an analytical survey with a cross-sectional design involving 46 respondents. The research was conducted at RSIA Ummuhani Purbalingga from January to June 2025. Sampling was conducted through direct observation and questionnaires (Google Forms). Data were processed using SPSS. Univariate analysis showed that respondents were aged 2535 years (76%) and 3645 years (24%), with 9% male and 91% female. Educational levels included Diploma III (55%), Bachelor of Nursing with professional degree (S. Kep., Ners) (43%), and Masters degree (2%). Length of work experience was 35 years (37%), 610 years (46%), and 1120 years (17%). Bivariate analysis using the chi-square test indicated no significant correlation between compliance and age (p = 0.743), gender (p = 0.152), education (p = 0.823), or length of work (p = 0.564). However, significant relationships were found for knowledge (p = 0.028), attitude (p = 0.006), and availability of facilities (p = 0.007). Knowledge, attitude, and supporting facilities are significantly associated with nurses compliance in performing hand hygiene. In contrast, age, gender, education, and length of work experience show no significant correlation.